Transformative medical ethics: A framework for changing practice according to normative–ethical requirements - Kuehlmeyer, Katja (Bioethics, 2024)
We propose a step-by-step methodological framework of translational bioethics that aims at changing medical practice according to normative–ethical requirements, which we will thus call “transformative medical ethics.” The framework becomes especially important when there is a gap between widely acknowledged, ethically justified normative claims and their realization in the practice of biomedicine and technology (ought–is gap). Building on prior work on translational bioethics, the framework maps a process with six different phases and 12 distinct translational steps. The steps involve various research activities including conceptual philosophical inquiry and (socio-)empirical research. On the one hand, the framework can be used as a heuristic tool to identify barriers to the transformation process. On the other hand, it can provide guidance for researchers and practitioners to develop appropriate (conceptual action and practice) models, which are then implemented and evaluated in specific practice contexts. We use the example of realizing the norm of respect for autonomy in the practice of medical decision-making to illustrate the framework. Further research is required, for example, to theoretically underpin the framework, to apply it to other ought–is gaps, and to evaluate its feasibility and effectiveness in various practice areas. Overall, the framework of transformative medical ethics suggests a strategic process to investigate and promote practice change that is ethically informed in all phases.